Model Implementasi Prinsip-prinsip Pendidikan Membentuk Ketauladanan Siswa - Mudasir Mudasir (AL-USWAH: Jurnal Riset dan Kajian Pendidikan Agama Islam, 2018)
This paper wants to explain the principles of education as a scientific discipline and its contribution mainly in shaping the exemplary of students. This paper departs from the discussion of the philosophy of goals and principles of Islamic education, then the basic concepts of the principles of Islamic education, and then the example of students. This discussion uses a philosophical approach by prioritizing religious principles. The results of this discussion found that in Islamic education there are integral principles, balanced, part of the rububiyah process, forming a whole human being, always related to religion, open, maintaining individual differences, and Islamic education is dynamic. These principles contribute to shaping student exemplary, which can be seen in terms of adhering to the discipline of learning in school, looking and dressing neatly, favored by all school communities, and active in various school activities.